A comparative analysis of lumboperitoneal shunt outcomes in patients with post-hemorrhagic and post-traumatic hydrocephalus - Tong Sun; Siyang Chen; Junjie Wang; Chao You; Ke Wu (Scientific Reports)
Abstract Hydrocephalus, whether arising from post-hemorrhagic or post-traumatic origins, poses significant challenges in clinical management. Lumboperitoneal shunting (LPS) emerges as a viable therapeutic intervention, yet comparative analyses between these etiologies remain scarce. This retrospective study aims to compare the efficacy and safety of LPS placement in patients with post-hemorrhagic (PHH) and post-traumatic hydrocephalus (PTH). This retrospective study investigates shunting outcomes in patients aged 18 years or older diagnosed with PHH or PTH who underwent LPS between 2014 and 2018. Primary outcomes included shunt reoperation rates, with secondary outcomes encompassing modified Rankin Scale (mRS) and National Institute of Health Stroke Scale (NIHSS) scores, Evans index, complications, and length of hospital stay. Favorable outcomes were defined as an mRS score of 2 or less. A total of 34 PHH and 48 PTH patients were included, with baseline characteristics being similar between groups. Shunt reoperation rates were comparable between PHH (23.5%) and PTH (27.1%) groups (P = 0.716). At 2 years, favorable outcomes were observed in 82.4% of PHH patients and 72.9% of PTH patients (P = 0.318). NIHSS scores at discharge (P = 0.230) and at 2 years (P = 0.530) showed no significant differences. However, PHH patients exhibited shorter hospital stays post-LPS implantation (P = 0.025). LPS placement demonstrates comparable outcomes in patients with PHH and PTH, with similar rates of shunt reoperation and complications, as well as equivalent neurological outcomes. However, Notably, PTH patients exhibited a higher risk of shunt malfunction compared to PHH patients, along with prolonged hospital stays post-LPS implantation.